Aplication of The SMARTER Method for The Selection of The Best Ambassador Brand - Nasib Marbun; Muhammad Zarlis; Rahmat Widia Sembiring (IJISTECH (International Journal of Information System and Technology), 2021)
This study aims to provide convenience for the company's management to solve problems in the process of selecting the best Brand Ambassador in promoting cosmetic tools. The problem identified in this study is the large number of prospective Brand Ambassadors, causing the management to find it difficult to determine the best Brand Ambassador. In this study, the decision support method applied is SMARTER which can determine the ranking results in the final decision using the level of importance of each parameter. The results of this study conclude that the selection of the best Brand Ambassador who is ranked first is A5 (Lucky) with a value of 0.653108466